The Influence Of Fintech Payment, Financial Literacy, And Financial Self-Efficacy On Financial Management Of Civil Servants Of The Ministry Of Law And Ham Pontianak - Sindi, Sindi; Ryanto, Fuad Ramdhan (UNIVERSITAS PAKUAN, 2024)
The rapid progression of digital technology has profoundly impacted financial behavior, especially via the extensive use of fintech technologies like pay-later services, mobile banking, and e-wallets. Although these technologies provide ease, they may also result in poor money management and impulsive spending. This research investigates the financial management practices of public officials in the Pontianak Ministry of Law and Human Rights concerning fintech payments, financial literacy, and financial self-efficacy. A quantitative associative methodology was used to collect data from 150 respondents selected via purposive sampling. The investigation, conducted using multiple linear regression, indicates that fintech payments, financial literacy, and financial self-efficacy significantly enhance financial management. The regression equation Y = 1.539 + 0.105X1 + 0.209X2 + 0.589X3 indicates that financial self-efficacy has the most substantial impact, followed by fintech payments and financial literacy. The findings suggest that fintech payments enhance transaction efficiency; yet, a lack of understanding and self-discipline may result in financial irresponsibility. Participants with improved financial literacy demonstrated advancements in planning, budgeting, and differentiating between requirements and wants. Likewise, those with heightened financial self-efficacy had more confidence in their financial management, leading to a decrease in impulsive spending. This study underscores the need of improving financial education and fostering self-efficacy to enable people to optimize the advantages of fintech while minimizing dangers. These findings provide significant insights for organizations and authorities seeking to enhance the financial welfare of government personnel in a more digital landscape.